Photochromic Dopamine Receptor Ligands Based on Dithienylethenes and Fulgides - Lachmann, Daniel; Studte, Carolin; Männel, Barbara; Hübner, Harald; Gmeiner, Peter; Koenig, Burkhard (Chemistry - A European Journal, 2017)
We describe the incorporation of the well-investigated class of photochromic dithienylethenes (DTEs) and fulgides into known dopamine receptor ligands such as 1,4-disubstituted aromatic and hydroxybenzoxazinone piperazines as well as aminoindanes. Subtype and functional selective photochromic ligands were obtained and characterized by NMR and UV/VIS spectroscopic measurements. The photophysical properties of the DTE based dopamine ligands revealed a high fatigue resistance for the diarylmaleimides, but the ringclosure could not be accomplished in polar solvents due to a known twisted intramolecular charge transfer (TICT). Several cyclopentene-DTEs showed high PSS, but a fast degradation by forming an irreversible byproduct. Focusing on the fulgides, high photostationary states and switching in polar solvents were possible. The compounds 43, 45 and 46 containing the isopropyl group showed only isomerization between the open E-form and the closed C-form. At a concentration of 1 nm, the cyclopentene-DTE 29-open showed a more than 11-fold higher activation of D-2S, a pharmacologically important G protein-coupled receptor, than its photochromic congener 29-closed. Interestingly, the fulgimide-based pair 52-(E)-open/52-closed could be discovered as an alternative photoswitch with inverse activation properties exhibiting four-fold higher activity in the closed state.
Keywords: dithienylethene; dopamine; fulgimide; gpcr; photoswitch